Activities of the wintering party at Syowa Station by the 31st Japanese Antarctic Research Expedition in 1990 - Yasuhiko Naito (National Institute of Polar Research, 1992)
Japanese Antarctic Research Expedition (JARE) dispatched two wintering parties to Syowa and Asuka Stations in Antarctica. The report describes the activities of the JARE-31 wintering party at Syowa Station. A total of 30 members, including 15 scientists and 15 logistics, had stayed at the station from 1 February 1990 to 31 Jaunary 1991. The major tasks assigned to the wintering party by the JARE headquarters were to conduct more than 60 items of the observation including launching of the ozone sonde and total ozone observation as a routine meteorological observation, STS earthquake observation, field experiments of ACR program with major focuss on the interaction between sea ice and atmosphere. EXOS-D and MOS-1 satellite observation and the experiments on penguin foraging ecology were also important programs. All these scientific experiments were performed successfully. The particular success of the field experiments of ACR was partly due to the better sea ice condition that guaranteed safe activities on sea ice throughout the year. Regarding the maintenance of the station, a new program on the waste disposal has started in relation to the conservation of the Antarctic environment. A large amount of the disposed waste was brought back to the country.